2018
DOI: 10.3390/md16030077
|View full text |Cite
|
Sign up to set email alerts
|

ATG5 Promotes Death Signaling in Response to the Cyclic Depsipeptides Coibamide A and Apratoxin A

Abstract: Our understanding of autophagy and lysosomal function has been greatly enhanced by the discovery of natural product structures that can serve as chemical probes to reveal new patterns of signal transduction in cells. Coibamide A is a cytotoxic marine natural product that induces mTOR-independent autophagy as an adaptive stress response that precedes cell death. Autophagy-related (ATG) protein 5 (ATG5) is required for coibamide-induced autophagy but not required for coibamide-induced apoptosis. Using wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Wan and colleagues also showed that coibamide A and apratoxin A, two cyclodepsipeptides isolated from cyanobacteria Leptolyngbya sp. and Lyngbya sp., respectively, induced caspase-dependent apoptosis preceded by autophagy [27]. Our study is consistent with their study since petromurin C-treated MV4-11 cells showed induction of autophagy at early time points followed by caspase-dependent and independent cell death at later times.…”
Section: Discussionsupporting
confidence: 92%
“…Wan and colleagues also showed that coibamide A and apratoxin A, two cyclodepsipeptides isolated from cyanobacteria Leptolyngbya sp. and Lyngbya sp., respectively, induced caspase-dependent apoptosis preceded by autophagy [27]. Our study is consistent with their study since petromurin C-treated MV4-11 cells showed induction of autophagy at early time points followed by caspase-dependent and independent cell death at later times.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of the induced autophagy on HUVEC cell viability is still to be investigated in the future. Using the mouse embryonic fibroblasts (MEFs) model two years later, the same group has shown that ATG5 is required for the cytotoxic activity of these depsipeptides, suggesting induction of cytotoxic autophagy [ 45 ]. Additionally, it was postulated that induced autophagy is not triggered by acute ER stress [ 45 ].…”
Section: Marine Compounds With a Validated Autophagy-modulatory Efmentioning
confidence: 99%
“…Autophagic cell death is not a common occurrence. While many marine natural compounds can affect autophagy either inducing it (chromomycin A2, psammaplin A, ilimaquinone [ 86 ], coibamide A, and apratoxin A [ 87 ]), or inhibiting it (manzamine A [ 88 ] and scalarin [ 89 ]), to our knowledge, only yessotoxin has been reported to induce autophagic cell death in glioma cell lines [ 90 ].…”
Section: Autophagy-dependent Cell Deathmentioning
confidence: 99%